2012
DOI: 10.1016/j.psyneuen.2011.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Inter-individual differences in trait negative affect moderate cortisol's effects on memory formation: Preliminary findings from two studies

Abstract: Acute emotional arousal moderates the effects of cortisol on memory. However, it is currently unknown how stable inter-individual differences (i.e., traits) moderate cortisol’s effects on memory. In two studies using within-subjects designs -- 31 healthy males in Study 1 and 42 healthy subjects (22 female) in Study 2 -- we measured trait negative affect (NA) and presented emotional and neutral pictures. In Study 1, we manipulated endogenous cortisol levels using a speech stressor following encoding. In Study 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
1
9
1
Order By: Relevance
“…It should be noted that Abercrombie and colleagues (2012a) found for men (compared to women) that trait emotional arousal operated differently as a moderator. In two studies, they found that cortisol elevation was related to memory facilitation in men who reported experiencing lower (not higher as in women) levels of trait emotional arousal.…”
Section: Personal Characteristics Alter Cortisol’s Effects On Learmentioning
confidence: 86%
See 2 more Smart Citations
“…It should be noted that Abercrombie and colleagues (2012a) found for men (compared to women) that trait emotional arousal operated differently as a moderator. In two studies, they found that cortisol elevation was related to memory facilitation in men who reported experiencing lower (not higher as in women) levels of trait emotional arousal.…”
Section: Personal Characteristics Alter Cortisol’s Effects On Learmentioning
confidence: 86%
“…However, only recently has research focused on how traits or lasting qualities (e.g., due to past experiences) moderate the effects of cortisol on learning (Abercrombie et al, 2012a; Bagot et al, 2009; Champagne et al, 2008). Evidence is emerging showing that lasting inter-individual differences due to variation in early life experiences and/or dispositional (“trait”) emotional arousal moderate cortisol’s effects on neuroplasticity and learning.…”
Section: Personal Characteristics Alter Cortisol’s Effects On Learmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical studies of depression and anxiety report a negative association of increased diurnal cortisol levels with weaknesses in both verbal and nonverbal memory (Gomez et al, 2009; Hinkelmann et al, 2009). Findings may reflect an additive effect of negative affect on alterations in HPA function in addition to the variance due to memory deficits (Buchanan et al, 1999; Abercrombie et al, 2012). The interaction of internalizing disorders with verbal memory in this study may also be partially related to the verbal demands of the TSST as suggested by similar findings in adults with lower educational levels and relative weaknesses in verbal abilities (Fiocco et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic corticosterone administration, similar to stress, was found to attenuate inhibitory GABAergic control to the BLA, leading to local neuronal hyperexcitability (Kavushansky and Richter-Levin, 2006;Rodriguez-Manzanares et al, 2005). Furthermore, clinical data suggest that the effect of cortisol on emotional memory depends on individual susceptibility (e.g., cortisol elevation was related to the facilitation of aversive memory formation in women with higher emotional arousal) (Abercrombie et al, 2012;van Ast et al, 2013). Based on this data, in the present study, we sought to test the hypothesis that animals more vulnerable to fear (HR rats) would be more sensitive to the effects of corticosterone on amygdala nuclei activity and fear memory and that this effect is accompanied by changes in the local expression of markers of neuronal and GABAergic system activity.…”
Section: Introductionmentioning
confidence: 99%